Aerobic fitness in male elite athletes aged 11-16 years: The influence of age, maturation parameters, and body composition - Noffz, J.; Hacke, C.; Weisser, B. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
INTRODUCTION: The relationship between age and aerobic capacity has been reported in a number of studies. The aim of this study was to consider the relationships between chronological age (CA), maturation parameters, body composition, and aerobic fitness in young male elite athletes. METHODS: 127 male subjects aged 11 -16 years were investigated. They were recruited during medical examinations for elite athletes or sent by their coaches from two local elite clubs (handball and soccer). Height and weight were measured with standard anthropometic methods. Body composition (muscle mass) was determined with eight-polar bioelectrical impedance analysis. During an incremental submaximal cycling exercise blood lactate concentration was measured and the performance at 4 mmol/l lactate was determined (OBLA). Maturity status was obtained by calculating the percentage of predicted adult height attained at the time of the study. In addition a prior validated questionnaire was used to determine the pubertal maturation (Pubertal Development Scale = PDS). Ethic approval was obtained from the Ethics in Human Research Committee of Kiel University/Medical Faculty. All athletes and their parents signed a consent form. RESULTS: 127 athletes were included, mean age 14,2 y, standard deviation; range (+/- 1,3; 11,0 -15,9), mean height was 170,8 cm (+/- 13,0; 137,0 - 194,0), mean percentage of predicted adult height was 93,7 % (+/- 6,3; 79 - 106), mean score in PDS was 12 (+/- 3,7; 5 - 19), mean muscle mass was 30,2 kg (+/- 7,55; 17,5 - 47,2), mean performance at OBLA was 149 Watt (+/- 35,4; 99 - 223). For all subjects, a significant relationship existed between aerobic capacity (OBLA) and age, muscle mass, percentage of predicted adult stature and pubertal development (p < 0,001). Using multiple regression analysis the model explained 53 % of the variance in exercise performance. Muscle mass was the only significant predictor for aerobic capacity. CONCLUSION: In the present study muscle mass had the predominant influence in aerobic fitness. The results highlighted the importance of considering the varieties of pubertal maturation for the assessment of aerobic exercise performance in young athletes. The muscle mass is an easy to gain, non-invasive marker. This information has to be considered when lactate thresholds are used to determine aerobic performance of adolescents.